2019
DOI: 10.3390/w11040779
|View full text |Cite
|
Sign up to set email alerts
|

Zootechnical Farm Wastewaters in Ecuador: A Treatment Proposal and Cost-benefit Analysis

Abstract: This paper presents and discusses the results of a study carried out in Ecuador, where the zootechnical sector represents one of the country’s most important economic activities. It is, however, the source of many environmental problems, including the release of untreated liquid effluents and odorous emissions, and the production and disposal of solid wastes. The main aim of this study was to propose a treatment train for the zootechnical farm wastewater, combining natural systems (i.e., lagoons and subsurface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The collected data are reported in Figures 8 and 9, grouped according to their class. [20,[24][25][26]40,43,45,46,48,49,55,59,60]. It emerges that the most frequently monitored classes were antibiotics (372 values), analgesics and anti-inflammatories (347 values), psychiatric drugs (155 values), and antivirals (154 values).…”
Section: Occurrence Of Micropollutants In Surface Water and Groundwatermentioning
confidence: 99%
See 2 more Smart Citations
“…The collected data are reported in Figures 8 and 9, grouped according to their class. [20,[24][25][26]40,43,45,46,48,49,55,59,60]. It emerges that the most frequently monitored classes were antibiotics (372 values), analgesics and anti-inflammatories (347 values), psychiatric drugs (155 values), and antivirals (154 values).…”
Section: Occurrence Of Micropollutants In Surface Water and Groundwatermentioning
confidence: 99%
“…It was found that the antivirals nevirapine, efavirenz, and the psychiatric drug carbamazepine, always occurred around 2-13 ng/L in different samples withdrawn from the Dam Hartbeespoort, Gauteng province, over the year It emerges that the most frequently monitored classes were antibiotics (372 values), analgesics and anti-inflammatories (347 values), psychiatric drugs (155 values), and antivirals (154 values). It was found that concentrations of pharmaceuticals may be very high in surface water: this occurs for acetylsalicylic acid (159,900 ng/L, [48]), ibuprofen (84,600 ng/L, [49]), clozapine (78,300 ng/L, [48]), phenacetin (68,300 ng/L, [40]), estriol (46,200 ng/L, [54]), caffeine (33,200 ng/L, [49]) and atenolol (30,000 ng/L, [24]). Most investigations noted that higher concentrations were found in winter than in summer depending on the typical consumption pattern.…”
Section: Occurrence Of Micropollutants In Surface Water and Groundwatermentioning
confidence: 99%
See 1 more Smart Citation
“…Net present value (NPV) and benefit-cost ratio (BCR) are calculated for the social costbenefit analysis of an environmental project [112,113]. The costs include initial investment and incremental operating and maintenance costs.…”
Section: Social Cost-benefit Analysismentioning
confidence: 99%
“…Livestock is one of the main economic activities in many countries worldwide and farm management can differ from country to country, as well as the management of the waste produced by the activities themselves, in particular zootechnical effluent (Verlicchi et al, 2019). The distribution maps of various livestock provided by FAO (Gilbert et al, 2018) show that the most common types of animal are cattle, followed by sheep and goats, swine, poultry and finally horses.…”
Section: Introductionmentioning
confidence: 99%